Comparison between amine-terminated phthalocyanines and their chlorambucil conjugates: Synthesis, spectroscopic properties, and in vitro anticancer activity. Issue 4 (26th January 2017) - Peng, Xiao-Hui; Chen, Shao-Fang; Zheng, Bi-Yuan; Zheng, Bing-De; Zheng, Qiao-Feng; Li, Xing-Shu; Ke, Mei-Rong; Huang, Jian-Dong
Abstract: Two amine-terminated phthalocyanines, including mono-α-substituted zinc phthalocyanine (ZnPc)4 and axially di-substituted silicon phthalocyanine (SiPc)6, as well as their chlorambucil (CLB) conjugates (5 and7 ) have been prepared. Both4 and6 show very high photocytotoxicities against HepG2 cells with IC50 values down to 31 nM and 9 nM, respectively. However, after conjugating with CLB, the anticancer activities of both conjugates, ZnPc-CLB5 (IC50  = 0.20 μM) and SiPc-CLB7 (IC50  = 17.47 μM), are greatly reduced as a result of their lower efficiency in fluorescence emission and singlet oxygen generation in aqueous solution. Moreover, both conjugates show significantly lower cellular uptake than their precursors, 4 and6 . Synergetic chemo-photodynamic therapy could not be observed on the two conjugates. Graphical abstract: Highlights: Two novel phthalocyanine-CLB conjugates (5 and7 ) have been synthetized. The structure-activity relationships of these compounds have been discussed. 6 and7 show weaker singlet oxygen generation efficiency than that of4 and5. Compound6 shows the highest photocytotoxicity against HepG2 cells (IC50  = 9 nM).